Detection of hydrogenated vegetable oils (vanaspati) in ghee using infrared spectroscopy - KUMAR, ARUN; LAL, DARSHAN; SETH, RAMAN (The Indian Journal of Animal Sciences, 2019)
Infrared spectroscopy, widely used for the characterization of cis- and transisomers of oils and fats, was used for the detection of adulteration in ghee with hydrogenated vegetable oils (Vanaspati) as the latter contains significantly higher levels of trans isomers formed during hydrogenation process used for vanaspati manufacturing. The average content of trans isomers (expressed as % trielaidin) in buffalo ghee, cow ghee and vanaspati as determined using infrared (IR) absorption at 10.36 Î¼ (965.25/cm) was 5.41, 6.82 and 37.05%, respectively. On the basis of increased level of trans isomers in ghee, as low as 5% addition of vanaspati to ghee could be detected easily.